2012
DOI: 10.1262/jrd.11-097n
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Protocol for Cryopreservation of Mouse Spermatozoa Using Cryotubes

Abstract: Abstract. The rapid increase in the number of genetically modified mouse strains has produced a high demand for their frozen spermatozoa from laboratories and mouse banking facilities. Historically, plastic straws have been used preferentially as containers for frozen mammalian spermatozoa because spermatozoa frozen in plastic straws have a high survival rate after thawing. However, plastic straws are more fragile and are used less often than the cryotubes used for conventional cell freezing. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Here, we have optimized the vitrification method developed by Jin et al [3] for efficient embryo cryopreservation using cryotubes so that the embryos could be cryopreserved more conveniently and transported for long distances more safely. Similarly, we have developed a freezing method for mouse spermatozoa optimized for cryotubes instead of plastic straws [13]. Nakao et al [14] previously developed an embryo vitrification method using cryotubes, but it needed a specific combination of a cooling device with a cryotube to keep the temperature inside the tubes at 0°C during storage.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have optimized the vitrification method developed by Jin et al [3] for efficient embryo cryopreservation using cryotubes so that the embryos could be cryopreserved more conveniently and transported for long distances more safely. Similarly, we have developed a freezing method for mouse spermatozoa optimized for cryotubes instead of plastic straws [13]. Nakao et al [14] previously developed an embryo vitrification method using cryotubes, but it needed a specific combination of a cooling device with a cryotube to keep the temperature inside the tubes at 0°C during storage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we used cryotubes as containers and found that the volume of the sperm suspension may critically affect the survivability of spermatozoa [11]. In this experiment, we used spermatozoa that had been frozen and stored in a 50 or 100 µl suspension, a volume larger than the optimal volume (10 µl).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we were able to increase the fertilization rates from 7% to 25% by using this method when spermatozoa had very poor motility (< 10% motility rate) because of inadequate freezing in cryotubes. We have previously reported that sperm cryopreservation using cryotubes was critically affected by the volume of the sperm suspension in a cryotube [11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spermatozoa from the epididymal caudae of male mice (3–15 months old) from each strain were suspended in 200 µl of sperm preincubation medium (HTF containing 0.4 mM methyl-β-cyclodextrin [17] , [18] and 0.1 mg/ml polyvinyl alcohol instead of BSA) and incubated at 37°C under 5% CO 2 in air for 45–60 min. Spermatozoa that had been frozen in plastic straws were thawed and preincubated as described previously until used for IVF [19] . At the time of insemination, the preincubated spermatozoa were transferred into 80 µl drops of fertilization medium containing cumulus-enclosed oocytes at a final concentration of 200–500 spermatozoa/µl.…”
Section: Methodsmentioning
confidence: 99%